Pemanfaatan Akun Twitter @PT_Transjakarta sebagai Sarana Komunikasi bagi Pengguna TransJakarta - Natania, Nasya; Nababan, Angel; Perry, Yoseph (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Public transportation is an alternative choice for many people in mobility, therefore it is natural for public transportation to provide optimal service for the comfort of users. One way to optimize service is to adapt to current technological developments. This form of adaptation can be seen in the use of social media as a medium for providing services to users of public transportation services. Social media not only encourages interaction activities, but also increases the city’s adaptability by utilizing online communication platforms. Transjakarta, as a mode of public transportation, uses social media as a communication platform to promote better Transjakarta services. Social media involves public organizations in providing opportunities for society to interact indirectly. This writing aims to find out the extent to which the PT_Transjakarta Twitter account is utilized as a medium that helps provide direction information for Transjakarta users. To answer this question, this research uses customer satisfaction theory. The method used is a qualitative method where the author will produce a more comprehensive study of a phenomenon as well as in-depth observations for Twitter users who use the @PT_Transjakarta twitter account. The use of social media in public transportation aims to provide services and information. Apart from that, with this article it is hoped that various other companies can imitate and implement the performance of the @PT_Transjakarta Twitter account in providing services to Transjakarta users via social media.